Static output feedback control of switched systems with quantization: A nonhomogeneous sojourn probability approach - Cheng, Jun; Park, Ju H.; Zhao, Xudong; Cao, Jinde; Qi, Wenhai (International journal of robust and nonlinear control, 2019)
Summary The present work deals with the problem of static output feedback control for discrete‐time switched systems (SSs) with quantization effects. Different from the existing results on SSs, a more general model with respect to a new switching rule (SR) is explored by utilizing a nonhomogeneous sojourn probability approach. Both control input and measured output are quantized by the mode‐dependent static logarithmic quantizers, respectively. To decrease the conservatism and eliminate the coupling parameters, a descriptor technology is employed in the static output feedback control scheme. In the framework of the time‐dependent SR, sufficient conditions are proposed to guarantee the mean square stability of resulting systems. Finally, an example is expressed to demonstrate the applicability and validity of the developed theoretical results.